Biomimicry Levels as an Approach to The Architectural Sustainability (Port Said Engineering Research Journal, 2014)
Certainly nature was and still the first teacher to humans and the main inspiration. Nature is a source of inspiration for architects as it is for scientists, for example: its consider source of inspiration for structures, building materials and systems of environmental and aesthetics. There aren‟t enough studies to conclude and devise solutions from nature to all areas of science and architecture. Branch of knowledge appeared called “Biomimicry” which mean (Nature Simulation) is an innovation method that seeks sustainable solutions by emulating nature's time-tested patterns . In this framework, research paper deals with nature as inspiration concept, Biomimicry concept, Biomimicry levels and approach in the field of architecture and The research presents a number of questions and try to answer them : What is Biomimicry? What are the Biomimicry Levels? How can use the Biomimicry to support Architectural sustainability ?????